Contamination of medical devices and hospital environments with free-living amoebae: Evidence from hospitals in Northwestern Iran - Hamed Behniafar; Adel Spotin; Ali Bahadori; Soghra Valizadeh; Leili Valizadeh; Hosein Pazoki; Fatemeh Mahdavi; Maryam Niyyati (PLoS ONE, 2026)
Free-living amoebae (FLAs) are ubiquitous protozoa found in soil, air, and artificial systems, including hospital environments. Some genera of free-living amoebae, such as Acanthamoeba , can cause severe health complications, including Acanthamoeba keratitis and granulomatous amoebic encephalitis. This study investigated the presence of free-living amoebae (FLAs) in hospital environments, including ready-to-use medical devices and equipment (such as lasers, swabs, and forceps), as well as beds and gowns. To the best of our knowledge, FLAs in these medical devices and equipment have been examined for the first time. In this cross-sectional study, 45 environmental and medical device samples were collected from two hospitals in Northwestern Iran. After filtration, the samples were cultured in a 1.5% non-nutrient agar medium enriched with Escherichia coli . The growth of the FLAs and their genera was determined through microscopic analysis. Positive samples were submitted for PCR analysis targeting the 18S rRNA gene, followed by sequencing and phylogenetic analysis. Also, the pathogenicity of Acanthamoeba isolates was evaluated through osmo- and thermotolerance tests. FLAs were detected in 22.22% (10/45) of samples using microscopy. Most of the examined sources (90%) had mixed contamination, including Acanthamoeba , Vahlkampfia , and Veramoeba (4), Acanthamoeba and Vahlkampfia (1), Acanthamoeba and Veramoeba (2), and Veramoeba and Vahlkampfia (2). Also, one source showed sole contamination with Vahlkampfia . Among the positive samples, 5 were obtained from environmental sources, 4 from equipment, and 1 from surgical gowns. Most Acanthamoeba isolates demonstrated osmo-tolerance (72.48% at 0.5 M) and thermo-tolerance (100% at 37°C).. Sequence analysis identified Acanthamoeba T4 genotype (5), Vahlkampfia sp. (3), and V. vermiformis (6). In this study, FLAs were isolated from patients’ beds and surgical gowns for the first time, emphasizing new infection risks within an ophthalmology hospital. In addition to the high prevalence of FLAs in the examined sources, most Acanthamoeba isolates were found to be resistant to osmotic stress and heat shock, which supports their pathogenic potential. However, these findings highlight the need for improved disinfection protocols for sterile equipment.